2012
DOI: 10.1007/s10803-012-1465-4
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Examining the Link Between Autistic Traits and Compulsive Internet Use in a Non-Clinical Sample

Abstract: Individuals with autism spectrum disorders or autistic traits may profit from Internet and computer-mediated interactions, but there is concern about their Internet use becoming compulsive. This study investigated the link between autistic traits and Internet use in a 2-wave longitudinal study with a non-clinical community sample (n = 390). As compared to people with less autistic traits, people with more autistic traits did not report a higher frequency of Internet use, but they were more prone to compulsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 21 publications
6
49
2
Order By: Relevance
“…This result regarding the relationship between autistic traits and Internet addiction was not consistent with previous studies using an adult sample, in which they found adults with more autistic traits predicted for Internet addiction (Finkenauer et al, 2012;Romano et al, 2013). To the best of our knowledge, this is the first study examining autistic traits and Internet addiction in children.…”
Section: Internet Addictioncontrasting
confidence: 97%
See 2 more Smart Citations
“…This result regarding the relationship between autistic traits and Internet addiction was not consistent with previous studies using an adult sample, in which they found adults with more autistic traits predicted for Internet addiction (Finkenauer et al, 2012;Romano et al, 2013). To the best of our knowledge, this is the first study examining autistic traits and Internet addiction in children.…”
Section: Internet Addictioncontrasting
confidence: 97%
“…Moreover, this unexpected predictability could be accounted for by poor academic performance, males, and protective parenting style. Unlike other studies that have found associations between Internet addiction, ADHD, and autistic traits without taking social adjustments into account (Finkenauer et al, 2012;Yen, Ko, Yen, Wu, & Yang, 2007). Our results suggest that effective evaluation and intervention of children and adolescents with ADHD and/or autistic traits for Internet addiction should be considered for its impact in the social context.…”
Section: Internet Addictioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Early evidence of adverse psychological impact was presented by Kraut and colleagues (1998) and by Young and Rodgers (1998), who found that frequent internet use raised the risk of depressive symptoms. Since then, studies have shown correlations of online activity by younger people with low self-esteem (Caplan 2002), loneliness (Clayton et al 2013), self-harm (Lam et al 2009) and autistic traits (Finkenauer et al 2012). However, other studies have indicated higher self-esteem and satisfaction with life, and reduced risk of mental health problems (Valkenburg et al 2006;Bessièrre et al 2008;Grieve et al 2013;Best et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some concern that, despite its benefits, the Internet has the risk of addictive use in this special group of people [50].…”
Section: High-risk Groups For Internet Addictionmentioning
confidence: 99%